Expressional of neurotrophins on neural tube defects the hub BDNF and NGF signaling pathways - Yang, Jinwei; Liu , Kuangping; Shen, Li; Ma, Wei (Journal of comprehensive Molecular science and genetics, 2024)
Objective: This study uses bioinformatics to analyze the differentially expressed genes (DEGs) in the NTDs. Methods: R software screens differentially expressed genes, and the WebGestalt functional enrichment analysis tool conducts Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomics (KEGG) pathway analysis. The Search Tool for the Retrieval of Interacting Genes/Proteins constructs protein interaction networks, and the cytoHubba plug‑in in the Cytoscape software predicts core genes. Subsequently, the NTD model of SD mouse was established and the tissues were isolated. BDNF, NGF, TrkA and TrkB were verified by immunofluorescence staining. Real‑time polymerase chain reaction assay and Western blotting assay were used to detect the mRNA and protein expression of BDNF, NGF, TrkA and TrkB. Results: A total 2057 DEGs were identified in the brain remnant tissue samples, including 1415 upregulated and 642 downregulated. A total of 2161 DEGs were identified in the spinal cord tissue samples, including 994 upregulated and 1067 regulated genes, a total of 239 commonly DEGs. GO and KEGG revealed among the 2057 DEGs in the brain remnant tissue samples, KEGG analysis found that they were enriched in the has0472 neurotrophic factor pathway, etc. GO analysis showed that the 2057 DEGs in the brain remnant tissue samples were involved in biological such as cognition, learning and learning or memory. Has04064 NF-κB signaling pathway, GO analysis showed that the 216 DEGs in the spinal cord tissue samples were involved in biological processes such as type I interferon signaling pathway. The BDNF/TrkB-MAPKPI3K-NF-κB signaling pathway is a classical signaling pathway that may play an important role in NTDs and deserves further exploration. 29 DEGs in the two groups. Upregulated and downregulated genes were mapped using the Search Tool for The Retrieval of Interacting genes /Proteins (STRING) (https://string-db.org/) based on the PPI network. Cytoscape (version 3.6, Beijing, China) software was used to the hub genes. The differential gene protein network of the neurotrophic factor signaling pathway and the NF-κB signaling pathway 35 nodes, 199 edges, an average node degree of 11.4, top10 genes obtained by the MCC algorithm are HRAS, TP53, PIK3R1, TRKA, NGF, BDNF and TRKB. Morphological changes in spinal cord neural tube malformations, PCR and WB results showed that BDNF, NGF, TrkA and TrkB were higher in the malformed group than in the control group. The BDNF and NGF signal pathways play an important role in the process of NTDs.